Cross-sectional Associations of Fatigue with Cerebral β-Amyloid in Older Adults at Risk of Dementia - Hooper, Claudie; De Souto Barreto, Philipe; Coley, Nicola; Cesari, Matteo; Payoux, Pierre; Salabert, Anne Sophie; Andrieu, Sandrine; Vellas, Bruno; , for the MAPT/DSA Study Group (Frontiers in Medicine, 2017)
Fatigue is a common symptom in the elderly and has also been associated with impaired cognition in older adults. Hence, we sought to explore the cross-sectional relationship between fatigue and cerebral beta-amyloid (Abeta) in 269 elderly individuals reporting subjective memory complaints from the Multidomain Alzheimer Preventive Trial (MAPT). Standard uptake value ratios (SUVRs) were generated by [18F] florbetapir positron emission tomography (PET) using the cerebellum as a reference. Cortical-to-cerebellar SUVRs (cortical-SUVRs) were obtained using the mean signal from the frontal cortex, temporal cortex, parietal cortex, precuneus, anterior cingulate, and posterior cingulate. Other brain regions independently assessed were the anterior cingulate, anterior putamen, caudate, hippocampus, medial orbitofrontal cortex, occipital cortex, parietal cortex, pons, posterior cingulate, posterior putamen, precuneus, semioval center and temporal cortex. Fatigue was defined according to two questions retrieved from the Center for Epidemiological Studies-Depression scale (CES-D). Chronic fatigue was defined as meeting fatigue criteria at 2 consecutive clinical visits 6 months apart between study baseline and 1 year (visits were performed at baseline, 6 months and 1 year then annually). We found no cross-sectional associations between fatigue assessed at the clinical visit closest to PET and Abeta in any brain region. Similarly, chronic fatigue was not associated with Abeta load. Sensitivity analysis in subjects with a CDR of 0.5 showed that fatigue reported at the clinical visit closest to PET was however weakly associated with increased Abeta in the hippocampus (B coefficient: 0.07, 95 % CI: 0.01,0.12, p = 0.016). These preliminary results suggest that fatigue might be associated with Abeta in brain regions associated with Alzheimer’s disease in subjects in the early stages of disease.